PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) PERUSAHAAN - Naufal Ade Septianto; Dul Muid (Diponegoro Journal of Accounting, 2020)
The aim of this study is to investigate how the different activities of corporate social responsibility affect corporate tax avoidance in basic industry and chemicals sector companies listed on the Indonesian Stock Exchange (IDX). This study uses the quantitative method to analyze the relationship between corporate social responsibility and corporate tax avoidance.The population of this research is the basic industry and chemicals sector companies on the Indonesian Stock Exchange (IDX) during the 2016-2018 period. The purposive sampling method is used to select the samples for the study. Based on a sample of 84 observation, this study finds that CSR environmental dimension is positively related to corporate tax avoidance. This indicates that companies with a higher score on CSR environmental dimension are more inclined to avoid corporate taxes. While CSR social dimension and CSR economic dimensions are negatively related to corporate tax avoidance.